1996
DOI: 10.1002/ss.37119967408
|View full text |Cite
|
Sign up to set email alerts
|

Employing noncognitive variables in admitting students of color

Abstract: Noncognitive variables have been shown to be valid predictors in selecting applicants of color. This chapter attempts to Jorge a link between admission and retention by describing how various retention efforts that derive from the noncognitive variables can be creatively implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The participants' affinity for a noncognitive conceptualizations of academic success over cognitive ones is of value. This finding was consistent with scholars' assertions of the value of noncognitive variables in determining academic success (Sedlacek, 1996;Sedlacek & Adams-Gaston, 1992;Tracey & Sedlacek, 1984). In addition, aspects of the Tinto's (1993) model of student departure may assist practitioners whom supervise, advise, teach, and/ or guide these persons academically.…”
Section: Practical Implicationssupporting
confidence: 83%
“…The participants' affinity for a noncognitive conceptualizations of academic success over cognitive ones is of value. This finding was consistent with scholars' assertions of the value of noncognitive variables in determining academic success (Sedlacek, 1996;Sedlacek & Adams-Gaston, 1992;Tracey & Sedlacek, 1984). In addition, aspects of the Tinto's (1993) model of student departure may assist practitioners whom supervise, advise, teach, and/ or guide these persons academically.…”
Section: Practical Implicationssupporting
confidence: 83%
“…For example, Sedlacek and Tracey have shown that noncognitive variables of students of color such as self confidence, dealing with racism, availability of strong support, and successful leadership experience as measured by the Noncognitive Questionnaire, correlate with the success of students of color more than the usual measures of standardized tests and grades (Sedlacek, 1996;Tracey & Sedlacek, 1987). Thus, colleges may well focus on developing such attributes as self confidence, leadership experience, support groups, and dealing with campus racism if more ethnic students are to succeed.…”
Section: Hispanic Studentsmentioning
confidence: 99%
“…Some minority groups, specifically African-American males, suffer from an educational system that is not developed optimally for minorities (Ting & Robinson, 1998). According to Sedlacek (1996), standardized tests that are used for admission to higher education institutions focus on intelligence areas that minorities typically do not develop, but are prevalent in male and female Caucasians. On average 51% of black males and 60% of black females usually score less than 700 on the SAT (Clark, Horton, & Alford, 1986) and ACT and SAT scores are generally better predictors for non-minority student athletes (Petrie & Russell, 1995).…”
Section: Ethnicitymentioning
confidence: 99%